Systematic Literature Review (SLR): Factors That Affect the Level of Taxpayer Awareness and Compliance in Paying PBB And BPHTB - Yuniar, Awaliyah Fadya; Lastari, Devi Suci; Situngkir, Tiar Lina; Ba’Gubair, Sana’a Mohammed Awwadh (Peneliti.net, 2025)
The PBB, also known as the Land and Building Tax, is a significant source of funding for public infrastructure projects that aim to enhance the welfare of the populace. In spite of this, there is still a relatively low level of compliance with property tax payments. This is caused in part by the public's negative attitude and lack of awareness as taxpayers, as well as in part by a lack of tax understanding. Therefore, the goal of this study is to examine the variables that affect taxpayer awareness and compliance with regard to building and land tax (PBB) payments and the acquisition fee for land and building rights (BPHTB). This research employs a systematic literature review (SLR) method, utilizing the PRISMA framework for reporting. The results of the study show that taxpayer awareness is significantly influenced by attitude, motivation, the family head's level of understanding, taxpayer perception of sanctions, and taxpayer education. Similarly, taxpayer compliance is influenced by taxpayer awareness, tax knowledge, service quality, income level, and perception of sanctions. Positive attitudes towards taxes and strong motivation positively influence taxpayer awareness. Likewise, taxpayer perceptions of the implementation of fine sanctions positively influence taxpayer awareness in PBB and BPHTB payments. Meanwhile, increasing taxpayer awareness through tax education has a positive impact on taxpayer compliance.